(3GdebGdGJ GdKdGK aj QaY GdCTjGA GdKbjdIs - (3bSWG Hf dhbG GdHYdHcj,J (B300 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI GdebGdI GdChdj ef cJGH GjQf aQ QaY jQjO Cf jMhd GdKbd GdeYdhe HGdbhI GdeYdheI s
(3BNQgG (B:s
(3HGdVQhQI eQI HYO eQI MJj jfMVQ GdchcH GdGfKj GdMaQ GdPj JQjO ajchf bO MaQfG GdchcH GdGfKj s
(3Vef eLehY , JQJjHgG (B: 1s
(3GeQ HENQGLI hJQLeJg GHh GdYHGS CMeO Hf GdeYJUes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B131s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
Keywords: (3eJaQbGJs